The notebook - Cassavetes, Nick (Barcelona Entertainment, 2004)
A poor yet passionate young man falls in love with a rich young woman, giving her a sense of freedom, but they are soon separated because of their social differences.
Gena Rowlands, James Garner, Rachel McAdams
Idiomas : Inglés Subt.: inglés
Keywords: Películas cinematográficas -- DVD